E-MODULE DEVELOPMENT OF IT-BASED DISCOVERY LEARNING APPROACH - Januardi; Heri Pratikto; Madziatul Churiyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study aims to develop an entrepreneurship e-Module based on IT-based discovery learning model approach and assess its impact on student engagement and learning outcomes. The research followed a research and development approach using the ADDIE model. Data was collected through observations, questionnaires, pretest and posttest assessments. The study comprised three stages: (1) Analysis of student learning needs, resulting in a draft e-Module; (2) Design and creation of a prototype e-entrepreneurship module using the Canva application; and (3) Thorough validation of the prototype by expert e-Module media validators and entrepreneurship subject matter experts. The developed entrepreneurship e-Module, structured around the IT-based discovery learning model, demonstrated high validity (4.34) during expert validation. In field tests, the module engaged 100 students and a small group of 8 students, leading to increased motivation and interest. In a class of 25 sixth-semester accounting education students, learning outcomes improved by 40% compared to the pre-e-Module phase. Student activity also notably increased, as indicated by observations and questionnaires. The integration of the entrepreneurship e-Module within the IT-based discovery learning model framework proved not only feasible but also highly effective in enhancing student engagement and learning outcomes.